Economic security specifics in the context of digitalisation - O. A. Ageeva; N. K. Kuchukova; Yu. D. Matytsyna (Вестник университета, 2022)
The article deals with the changing approaches to economic security of economic entities in the context of digital technologies, which increase risks and create new threats to achieving the goals set by enterprises and organisations. This article explores the external and internal factors that affect the economic security of an enterprise in the context of digitalisation, and offers recommendations for reducing risks in this area. The study based on an analysis of global trends in the implementation of digital technologies in enterprises and organisations and the study of reviews by consulting firms and extensive scientific literature in this area. The authors propose new approaches for the implementation of digital technologies in enterprises, which will have reduced risks and improve their economic security. The main trends in the digital environment development have been identified; threats that may affect the economic security of financial and economic activities of market subjects have been identified, and ways to reduce the risks to their economic security under digitalisation have been proposed.